Pendampingan Usaha Mikro dalam Upaya Meningkatkan Penjualan melalui Digitalisasi - Trisni Handayani; Kholifaturrossidin Kholifaturrossidin; Firman Ihsan Herditya; Muhammad Ammar Fadgham (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
MSMEs in Indonesia play an important role in building the country's economy. There are many obstacles in doing business, especially in MSMEs, such as experiencing a decrease in turnover to closing their business. One of the business hurdles faced is the lack of access to large markets and the lack of skills in utilizing digital technology to expand markets and increase income. The method used in this research is a mentoring method in the form of introducing digitalization in MSMEs. The stages of this mentoring activity begin with observation, interviews, and mentoring. Digital-based MSMEs are businesses that use digital technology, not only in the marketing sector but all business processes of these MSMEs. Digital-based MSMEs are a sector that is growing rapidly due to the adoption of information technology and the internet. The conclusion from the discussion above is the importance of assistance to micro businesses (MSMEs) in facing technological advances by using digitalization to increase sales. However, one of the challenges in this assistance is the lack of technological literacy and limited capital.